Engineering the Reststrahlen band with hybrid plasmon/phonon excitations. (28th December 2015) - Streyer, W.; Feng, K.; Zhong, Y.; Hoffman, A.J.; Wasserman, D.
Abstract: Abstract : There has been increasing interest in so-called phononic materials, which can support surface modes known as surface phonon polaritons, consisting of electromagnetic waves coupled to lattice vibrations at the surface of a polar material. While such excitations have a variety of desirable features, they are limited to the spectral range between a material's longitudinal and transverse optical phonon frequencies. In this work, we demonstrate that for materials whose free-carrier concentrations can be controlled, hybrid plasmonic/phononic modes can be supported across a range of frequencies including those generally forbidden by purely phononic materials.